(untitled) (Eurasian Journal of Ecology, 2016)
This article is focused on review of legislative and regulatory requirements for ecological monitoring conducted by nature users in Kazakhstan, rules on organization and conducting baseline studies and compliance monitoring during oil operation in Kazakhstan sector of the Caspian Sea.